Degradação de efluentes têxteis pelos processos foto fenton e redutivo, utilizando-se ferro proveniente de descarte de atividade mineradora - Donadia, Jaqueline Frigerio (2011)
Several problems involving the treatment plants of textile effluents, especially the low level of color removal efficiency. The application of conventional biological methods for textile effluents treatment is limited by poor degradation of some dyes, generating toxic substances such as aromatic amines with carcinogenic potential. Thus, heterogeneous photocatalysis is an alternative in the treatment of this effluent. This study investigated the treatment of this kind of effluent employing as catalyst in reductive and oxidative processes, an iron residue that is often produced by ornamental rocks industry in Nova Venécia -ES. The residue was characterized by X-ray diffraction, Mössbauer Spectroscopy, Scanning Electron Microscope(SEM)andDicromatometry.The reagentsquantities were otimized and the results showed that in both systems, it is observed degradation above 98,00%. The reductive process alone reduced the organic load in 74,30% for the synthetic effluent and 73,20% for the real effluent. In addition, mineralization in the order of 61,20% for the synthetic effluent and 60,30% for real effluent. It stands out the association between oxidative and reductive processes, which also allows more than 98,00% degradation and reduction oforganic matter in the form of chemical oxygen demand (COD) in the range of 77,50%the synthetic effluentand 76,50% forthe real . In addition, there is a total organic carbon(TOC) reduction of 62,80% for the synthetic effluent and 56,50% for the real in reaction time of 120 minutes. Furthermore,foranalysisbyGCMS, notoxic substances were detected.It is noteworthy that the reductive system presented better cost effectiveness. Given the above, it is possible to conclude that the systems described inthis work are presented as a promising alternative for the textile effluent treatment through sustainability, in which a waste deals with another one.